PENGARUH EARNING PER SHARE, DEBT TO EQUITY RATIO, RETURN ON ASSET DAN RETURN ON EQUITY TERHADAP RETURN SAHAM PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Aldi Fradana, Nodia Fredita; Widodo, Agustina (Jurnal Bina Manajemen, 2023)
This study aims to prove the effect of EPS, DER, ROA and ROE on stock returns innfood and beverageecompanies listed on the Indonesia StockkExchange. The populationnused in this study is foodaand beverage companiesslisted onnthe IndonesiaaStock Exchange for the 2015-2021 period. Theesample technique uses purposiveesampling. Data analysis technique using multiple linear regression analysis. The results showed that EPS and DER had no significant negative effect on stock returns, ROA and ROE had nosignificant positive effect on stock returns. The value of Adjusted R² is 0.041, which means that the 4.1% variation in stock returns for food and beverageccompanies listed on the IndonesiaaStock Exchange can be explained by the four independent variables, namely EPS, DER, ROA and ROE. While the remaining 95.9% is explained by other variables not examined in this study.